2008
DOI: 10.1103/physreve.77.051114
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational dynamics of an infinite shuffled lattice: Early time evolution and universality of nonlinear correlations

Abstract: In two recent articles a detailed study has been presented of the out of equilibrium dynamics of an infinite system of self-gravitating points initially located on a randomly perturbed lattice. In this article we extend the treatment of the early time phase during which strong non-linear correlations first develop, prior to the onset of "self-similar" scaling in the two point correlation function. We establish more directly, using appropriate modifications of the numerical integration, that the development of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
(88 reference statements)
1
2
0
Order By: Relevance
“…In [36] we have examined the issue of the resultant errors, placing non-trivial lower bounds on them which show that they are certainly at a level relevant to the precision required in coming years for these simulations. In our study of the SL in [29] we have shown that the asymptotic form of the correlation function in this case is very similar to that which emerges at early times when the evolution is clearly far from the VP limit. This suggests that careful further study of the relation between the two regimes, < ε and > ε, even if numerically costly, will be necessary to resolve these issues, which are of both theoretical and practical importance in the theory of structure formation in the universe.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In [36] we have examined the issue of the resultant errors, placing non-trivial lower bounds on them which show that they are certainly at a level relevant to the precision required in coming years for these simulations. In our study of the SL in [29] we have shown that the asymptotic form of the correlation function in this case is very similar to that which emerges at early times when the evolution is clearly far from the VP limit. This suggests that careful further study of the relation between the two regimes, < ε and > ε, even if numerically costly, will be necessary to resolve these issues, which are of both theoretical and practical importance in the theory of structure formation in the universe.…”
Section: Discussionsupporting
confidence: 68%
“…In the set of initial conditions that we have discussed, we have, as we discussed, only a single parameter, the normalized shuffling δ. It is straightforward to see that variation of this parameter does not give convergence to the VP limit (just as variation of the single parameter N in the finite case did not define such convergence): at any value of δ an analysis of the dynamics (see in particular [29]) shows that there is always a phase of the evolution at early times in which the forces on particles are determined predominantly by their nearest neighbors, which means that the mean-field VP limit is certainly not valid. Further for small values of δ one can show, using a perturbative treatment of the dynamics, that there are measurable deviations from the fluid linear theory limit at any wavenumber k [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation